Clinical features and responses to eculizumab of paroxysmal nocturnal hemoglobinuria patients: A single-center experience - Ekinci, Omer; Demircioğlu, Sinan; Sonmez, Gulcin Miyase; Demir, Cengiz (My University, 2019)
Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired clonal hematopoietic stem cell disease classically characterized by chronic intravascular hemolysis, bone marrow failure, and thrombosis. Eculizumab is an anti-C5 monoclonal antibody proven to reduce hemolysis and thrombotic attacks in the treatment of PNH. We aimed to present our data on PNH, a rare disease, and to share our experiences treating PNH with eculizumab. Demographic data, clinical features, history of thrombosis, responses to eculizumab treatment, and survival rates of 9 patients diagnosed with PNH at our hematology center were retrospectively analyzed. The median follow-up period was 46 months (range: 25-62). Five of the patients were female (55.5%), and 4 were male (44.5%), with a median age of 33.5±12.3 years. The mean hemoglobin level was 8.2 g/dL (5.7–10.1 g/dL), mean leukocyte count was 5.80x103/?L (1.72x103/?L–8.30x103/?L), mean platelet count was 96.6x103/L (42x103/?L–214x103/?L), mean lactate dehydrogenase level was 1312 U/L (423–2690 U/L), and mean reticulocyte level was 3.76% (1.1–6.3%). In our study, all cases received eculizumab therapy, of which 8 exhibited full or partial responses, while one was unresponsive to treatment. All patients were alive after the follow-up period. In 8 of the nine patients treated with eculizumab, hemolysis decreased following treatment and blood transfusion was not necessary. The quality of life experienced by all patients was improved. Following determination of the pathogenesis of the PNH, besides the classical treatment methods, eculizumab is a popular treatment option.
Keywords: Genel ve Dahili Tıp; Hematoloji